Molecular Markers for Septoria Leaf Spot (Septoria lycopersicii Speg.) Resistance in Tomato (Solanum lycopersicum L.) - Joshi, Bal K; Louws, Frank J; Yenco, G Craig; Sosinski, Byron R; Arellano, Consuelo; Panthee, Dilip R (Nepal Journal of Biotechnology, 2015)
Marker assisted selection (MAS) has not been initiated in tomato (Solanum lycopersicum L.) for septoria leaf spot (SLS) resistance caused by Septoria lycopersici Speg due to lack of molecular markers. We studied the inheritance of SLS resistance and identified molecular markers linked to SLS resistance using bulked segregant analysis (BSA) in a segregating F2 population. Tomato inbred lines, NC 85L-1W (2007), susceptible to SLS and NC 839-2(2007)-1, resistant to SLS were used to develop the segregating population. A total of 250 F2 plants, and 10 plants each of P1, P2 and F1 were grown at the Mountain Horticultural Crops Research and Extension Center (MHCREC), Mills River NC in the summer of 2009. Disease severity was scored using a scale of 0 to 5, where 0 = no disease and 5 = complete development of disease. DNA was extracted from 2-3 week old plants and parental lines were screened with a total of 197 random amplified polymorphic DNA (RAPD) primers, of which 34 were polymorphic. Two DNA bulks, called resistant bulk (RB) and susceptible bulk (SB) were prepared from the F2 individuals. The RB and SB consisted of 8 individuals each with disease scores of 0, and 4.0 or 4.5, respectively. The segregation ratio of resistant and susceptible plants in F2 generation fit the expected Mendelian ratio of 3:1 for a single dominant gene. Five RAPD markers were linked to the SLS disease reaction, of which two were linked to susceptibility and three to the resistance. Subject to verification in independent populations, these markers may be useful for MAS of SLS resistance in tomato. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 40-47